The radio station broadcast, satellite & internet - Keith, Michael C. 1945- (Focal Press, 2010)
"This book is bible for beginning radio professionals: the complete, definitive guide to the internal workings of radio stations and the radio industry. Not only will you begin understand how each job at a radio station is best performed, you will learn how it meshes with those of the rest of the radio station staff. If you are uncertain of your career goals, this book provides a solid foundation in who does what, when, and why. The Radio Station details all departments within a radio station"--EBL.
Includes bibliographical references and index. - Print version record
Keywords: Radio stations; Radio broadcasting; Radio; Stations de radio; radio stations; TECHNOLOGY & ENGINEERING; Radio